FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi pada Kantor Akuntan Publik di Jawa Tengah dan D.I.Y) - Rian Ronaldy Lenggu, 12.05.52.0148; Himmawan Dwi Nugroho, Arief (Students' Journal of Accounting and Banking, 2018)
This research was motivated by the behavior of auditors in auditing the financial report of clients.The purpose of this study was to analyze the effect of time pressure, audit risk, premature termination of audit procedures, quality review and control procedures and locus of control on premature termination of audit procedures. The population in this study is the auditor who works at the Public Accounting Firm (KAP) in Semarang. The sampling technique using the convinence sampling method based on the auditor who is in the Public Accountant Office obtained a sample of 52 respondents. Data used in the form of questionnaire primary data. Data analysis used linear regression analysis. Based on the results of the study it can be seen that time pressure, materiality and locus of control have a positive effect on premature termination of audit procedures. While audit risk and quality review and control procedures negatively affect premature termination of audit procedures. Keywords: time pressure, audit risk, materiality, quality review and control procedures, locus of control and premature termination of audit procedures.